2007
DOI: 10.1172/jci30674
|View full text |Cite
|
Sign up to set email alerts
|

Maternal disturbance in activated sphingolipid metabolism causes pregnancy loss in mice

Abstract: Uterine decidualization, a process that occurs in response to embryo implantation, is critical for embryonic survival and thus is a key event for successful pregnancy. Here we show that the sphingolipid metabolic pathway is highly activated in the deciduum during pregnancy and disturbance of the pathway by disruption of sphingosine kinase (Sphk) genes causes defective decidualization with severely compromised uterine blood vessels, leading to early pregnancy loss. Sphk-deficient female mice (Sphk1 -/-Sphk2 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 55 publications
4
119
0
2
Order By: Relevance
“…Moreover, Michaud et al (2006) measured S1P levels in forepaw tissue and found only slight decreases in SK-1-deficient mice. Recently, Mizugishi et al (2007) generated SphK1 -/-SphK2 q/-mice and investigated uterine decidualisation. When measuring S1P levels in uteri, there was no difference between wild-type and SphK1 -/-SphK2 q/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Michaud et al (2006) measured S1P levels in forepaw tissue and found only slight decreases in SK-1-deficient mice. Recently, Mizugishi et al (2007) generated SphK1 -/-SphK2 q/-mice and investigated uterine decidualisation. When measuring S1P levels in uteri, there was no difference between wild-type and SphK1 -/-SphK2 q/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…5 ) ( 126 ). S1P regulates embryonic nervous system development, as the neuroepithelial layers of the developing telencephalon in S1pr1 Ϫ / Ϫ embryos have signifi cantly increased apoptosis and decreased mitosis ( 127 ). S1P 2 may also play a role in regulating neural progenitors, as postischemic administration of the S1P 2 antagonist JTE-013 or short hairpin RNA against S1P 2 signifi cantly increased progenitor migration to the ischemic region ( 128 ).…”
Section: Nervous Systemmentioning
confidence: 99%
“…For example, it was recently demonstrated that a number of genes involved in sphingolipid metabolism were highly upregulated in the mouse decidua, and that disruption of sphingolipid metabolism caused pregnancy loss in mice (Mizugishi et al 2007). In addition, prosaposin, an accessory molecule essential for glycosphingolipid loading onto CD1d (Kang and Cresswell 2004;Zhou et al 2004) is known to be expressed at high levels in the decidua (Sun et al 1994).…”
Section: Nkt Cells and Cd1d At The Maternal-fetal Interfacementioning
confidence: 99%